ARDS complicating pustular psoriasis: treatment with low-dose corticosteroids, vitamin C and thiamine. (2nd February 2018) - Marik, Paul Ellis; Long, Ashleigh
Abstract : We report the case of a 45-year-old Caucasian woman with a history of psoriasis, admitted to our Medical intensive care unit following the acute onset of diffuse rash and progressive dyspnoea and hypoxaemia requiring escalating respiratory support (continuous positive airway pressure of 10 cm H2 O). Her chest X-ray was consistent with findings of non-cardiogenic pulmonary oedema. Echocardiogram was normal. Dermatology considered her skin lesions to be consistent with psoriasis vulgaris with pustular flare. In the absence of an identifiable cause for her respiratory failure, she was diagnosed with acute respiratory distress syndrome due to her psoriatic flare. Treatment with cyclosporine was initiated together with low-dose systemic corticosteroids, intravenous vitamin C and thiamine. The patient made a dramatic recovery being weaned to nasal cannulae within 24 hours after the initiation of this treatment protocol and was discharged home a few days later.